2006
DOI: 10.1542/peds.2006-0682
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Energy Gap Among US Children: A Counterfactual Approach

Abstract: Quantifying the energy imbalance responsible for recent changes in weight distribution among children can provide salient targets for population intervention. Consistent behavioral changes averaging 110 to 165 kcal/day may be sufficient to counterbalance the energy gap. Changes in excess dietary intake (eg, eliminating one sugar-sweetened beverage at 150 kcal per can) may be easier to attain than increases in physical activity levels (eg, a 30-kg boy replacing sitting for 1.9 hours with 1.9 hours walking for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
179
2
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(189 citation statements)
references
References 46 publications
5
179
2
3
Order By: Relevance
“…While it is not possible to compare these studies directly, the estimates are consistent with population weight gain being driven by a relatively small excess in consumption over the requirement for basal metabolism and habitual energy expenditure. Wang et al 25 and van den Berg et al 26 have reported comparable studies in children. The former, using data from the US National Health and Nutrition Examination Surveys from 1988–1994 and 1999–2002, estimated that an energy gap of between 0.46 and 0.69 MJ/day could have prevented the weight gain seen over this 10‐year period.…”
Section: Resultsmentioning
confidence: 83%
“…While it is not possible to compare these studies directly, the estimates are consistent with population weight gain being driven by a relatively small excess in consumption over the requirement for basal metabolism and habitual energy expenditure. Wang et al 25 and van den Berg et al 26 have reported comparable studies in children. The former, using data from the US National Health and Nutrition Examination Surveys from 1988–1994 and 1999–2002, estimated that an energy gap of between 0.46 and 0.69 MJ/day could have prevented the weight gain seen over this 10‐year period.…”
Section: Resultsmentioning
confidence: 83%
“…It is necessary to consider that the energy imbalance is already expected due to the extra energy costs required for the intense anabolic process of growth, which implies in persistent positive energy balance. It should, therefore, separate the characteristic energy accumulation for growth and the excessive energy intake (18,21,22) . During the stage of growth and development, differences in the body composition and in the degree of energy accumulation by age, height, gender, ethnicity and pubertal stage are usually expected (21,23) .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (18) considered the extra energy necessary for normal growth, but this study was limited by its cross sectional design. The long-term prospective studies performed by Plachta-Danielzik et al (19) and van den Berg et al (20) took into consideration the limitations of the prior studies, and were able to provide more accurate estimates of the energy gap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations